Contribuição ao conhecimento químico de plantas do nordeste:Andira surinamensis e Piper divaricatum - Almeida, José Gustavo Lima de (2007)
This work describes the phytochemical investigation of extracts from the branch wood and branch barks of Andira surinamensis (Leguminosae), as well as, the volatile chemical composition of essential oil from leaves and fruits of Piper divaricatum G. Mey (Piperaceae). The phytochemical investigation of A. surinamensis extracts, using classic methods of chromatography on silica gel, yielded a novel isoflavone dimer, 4’-methoxyisoflavone-(7-O- 7’’)-3’’’,4’’’-methylenedioxyisoflavone (surinamensin), along with the triterpene lupeol and the known isoflavones 5,7-dihydroxy-4\\\'-methoxyisoflavone (biochanin A), 5,4\\\'-dihydroxy-7- methoxyisoflavone (prunetin), 7,3’-dihydroxy-4’-methoxyisoflavone (calycosin) and 5,7,3’- trihydroxy-4’-methoxyisoflavone (pratensein). The structures of all isolated compounds were elucidated by spectroscopic methods, such as MS, IR and particularly 1D and 2D homonuclear and heteronuclear NMR spectroscopy and, comparison with published data for closely related compounds. The chemical composition of the essential oils from leaves and fruits of Piper divaricatum G. Mey., was analyzed by GC/MS and GC-FID. Twenty-four components, representing more than 94.0% of the chemical compositions of the oils, were identified. Both oils showed higher concentrations of monoterpenoids, particularly the oils from leaves (81.1%). The oils showed some compositional similarities but the fruit oil could be easily distinguished from the leaf oil by the exclusive presence of a-phellandrene (4.60%), (E)-muurola-4(14),5-diene (9,0%) and significant content of (E)-caryophyllene (11.4%). The major constituents of the leaf oils were linalool (23.4%), b-pinene (25.3%) and a-pinene (18.8%), while the fruit oils of the fruits contained b-pinene (18.0%) and a-pinene (17.6%) and (E)-caryophyllene (11.4%) as prevalent compounds.